Syn i ojciec w „Bojaźni i drżeniu” Sørena Kierkegaarda - Szabat, Marta (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
This article concerns events of the Old Testament – Yahweh commands Abraham to sacrifice his only son – Isaac – on Mount Moriah. This passage from the Old Testament, from the Book of Genesis, became the basis of Søren Kierkegaard’s considerations in Fear and Trembling. In the text I refer to, on the one hand, Kierkegaard’s considerations, while on the other hand I try to identify other possible interpretive tropes that could be useful, for example, during classes on the subject of faith or the status of ethical dilemmas in the modern world.